Nanoscale Poling of Polymer Films1. (20th February 2013) - Castagna, Riccardo; Milner, Alexander; Zyss, Joseph; Prior, Yehiam
<x xml:space="preserve">Abstract</x> Spots of second harmonic generation (SHG) are produced from nanopatterned sub‐micrometer areas of nonlinear polymer media. Information is written by using a biased‐AFM tip, a highly nonlinear polymer (poly(methyl metha‐acrylate)‐co‐Disperse Red 1), and a novel "floating‐tip nanolithography" (FTN) technique. Dipoles are oriented and aligned at the nanoscale under the biased‐AFM tip, resulting in SHG production. The information is storable over weeks. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>